Особенности размещения и численность некоторых млекопитающих Среднего Приднепровья - Бойко, Н.Я.; Самарский, С.Л. (Вестник зоологии, 1970)
Исследованы особенности распространения и численность хищных млекопитающих Среднего Приднепровья (Полтавская, Черкасская и Кировоградская области) — лисицы обыкновенной, барсука, куницы лесной, хорьков лесного и степного. Установлено, что численность и плотность популяций хищных млекопитающих определяются наличием оптимальных защитных условий, устойчивой кормовой базы и степенью охвата промыслом. The peculiarities of placing and quantity of predatory mammals were investigated at the territory of the Middle Dnieper area.
It was established that quantity and density of populations of predatory mammals is determined by the presence of optimal protecting conditions, stable food reserve and degree of hunting.
Vulpes uulpes, Maries foina, Mustella pulorius and other animals accomodated to the existence in cultural landscape. They find here shelters and a sufficient amount of food.
Meles metes, Martes martes and Mustella eversmanni as a result of deterioration of protecting conditions and intensive hunting are met rarely at the investigated territory and require a strict protection.